2023
DOI: 10.3390/lubricants11050201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Chemically Degraded Lubricant’s Impact on Spur Gear Wear

Abstract: The impact of lubricating oil degradation, which can happen during both storage and use, on spur gear wear is thoroughly examined in this paper at all scales, from macro to nano. A thorough structure was created by combining the results of testing performed at the macroscale on a test rig and at the nanoscale using tools such as FESEM analysis. Using a single-stage spur transmission under two different working conditions ('40Nm, 1200rpm, 198 hours' and '50Nm, 500rpm, 90 minutes'), macroscale experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This dependence shows the importance of acidity changes for heavily loaded friction pairs. A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28]. The aging of lubricants causes the change in the lubricants' chemistry and the compounds formed at the friction A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28].…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dependence shows the importance of acidity changes for heavily loaded friction pairs. A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28]. The aging of lubricants causes the change in the lubricants' chemistry and the compounds formed at the friction A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28].…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28]. The aging of lubricants causes the change in the lubricants' chemistry and the compounds formed at the friction A considerable number of studies shows the direct correlation between oil deterioration and the reducing tribological efficiency of lubricants [26][27][28]. The aging of lubricants causes the change in the lubricants' chemistry and the compounds formed at the friction surface [29].…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…To deal with this problem, some companies recondition the lubricants to give them a "new use", but they basically separate the wear debris particles and incorporate some additives without any standard parameter about this process. Likewise, recent investigations are focused on studying the effect of degradation on lubricating performance [5] and finding different ways to reuse degraded lubricants [6]. The interesting results of [5,6] have demonstrated that by the incorporation of nano-additives, the acidification, pH value, and wear responses can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, recent investigations are focused on studying the effect of degradation on lubricating performance [5] and finding different ways to reuse degraded lubricants [6]. The interesting results of [5,6] have demonstrated that by the incorporation of nano-additives, the acidification, pH value, and wear responses can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [6] have researched the lubrication of tooth surfaces with groove textures to reduce friction. In recent years, research on gear lubrication has further expanded to encompass thermal elastohydrodynamic lubrication [7,8] and the study of lubricants [9,10]. Sivayogan et al [11] have further studied the transient non-Newtonian elastohydrodynamics of rough meshing tooth surfaces under complex contact kinematics.…”
Section: Introductionmentioning
confidence: 99%